Perspektif Mahasiswa terhadap Pengunaan Medsos dan Prestasi Belajar Mahasiswa - Sari, Diah Pita; Diva, Andini Tiara; Styaningrum, Fani Kusuma; Gaoma, Akin Witri; Fawniaia, Nabila Olga; Nugraha, Joko Tri (ANTASENA: Governance and Innovation Journal, 2025)
The digital era has significantly transformed how university students access and manage academic information, with social media becoming an increasingly dominant platform. This study aims to examine the relationship between the frequency of social media usage and students’ academic achievement. Adopting a quantitative approach, the research utilized a survey method involving 100 students from various study programs selected through simple random sampling. Data were collected using a structured questionnaire measuring the intensity of social media use (Instagram, WhatsApp, TikTok, and Facebook) alongside students' Grade Point Average (GPA) as an academic performance indicator. The Pearson correlation test was employed to analyze the relationship between variables. Findings reveal a statistically significant correlation between social media usage and academic achievement, with the strength and direction of the relationship varying depending on the platform and usage intensity. Moderately directed use of social media contributes positively to information access and collaborative learning, while excessive use negatively impacts concentration and academic outcomes. This study underscores the importance of promoting digital literacy and effective time management among students. The results suggest the need for adaptive, technology-integrated learning strategies and institutional policies that support the positive integration of digital platforms into educational practices. These insights offer valuable contributions to the discourse on optimizing digital behavior for academic success in higher education.